Systematics of New Guinea treefrogs (Litoria: Pelodryadidae) with erectile rostral spikes: an extended description of Litoria pronimia and a new species from the Foja Mountains - Oliver, Paul M.; Günther, Rainer; Mumpuni, Mumpuni; Richards, Stephen J. (Zootaxa, 2019)
A small number of treefrog species (Litoria) from Melanesia are unusual amongst Anura in having distinctive fleshy rostral spikes. Here, we first present an extended description for Litoria pronimia Menzies, a small species that is widespread along the southern edge of the Central Cordillera of New Guinea, and in which males have a long and erectile rostral spike. Second, we describe Litoria pinocchio sp. nov. a new, morphologically similar, yet geographically disjunct species from the Foja Mountains in northern Papua Province, Indonesia. The new species differs from Litoria pronimia in aspects of body shape, proportions and colouration. A review of variation in the size, structure and degree of sexual dimorphism of the rostral spike across different species of Litoria suggests varying function including mate selection and camouflage.